Provincial justice : Upper Canadian legal portraits from the Dictionary of Canadian biography - Fraser, Robert L. (Robert Lochiel) (Published for the Osgoode Society by University of Toronto Press, 1992)
In the formative years of Ontario's history, the law loomed large, as a profession, a preoccupation of legislators, a subject of debate and controversy, and a force that many citizens found themselves up against. Robert Fraser has drawn from the pages of the Dictionary of Canadian Biography the stories of sixty people who played a key role in the legal history of Upper Canada.Told in a readable style that has been much praised, these profiles contain information that bears the authoritative stamp of the DCB volumes from which they come. They add a valuable personal dimension to Ontario's legal history.